Luisa Tetrazzini : the Florentine nightingale - Gattey, Charles Neilson (Opera biography series ;, 1995)
This book, the result of many years' research in Europe, America and Russia, is the first biography of the diva whom Adelina Patti named as her successor. Tetrazzini's extraordinary life is revealed for the first time, correcting much of the published information about her. For example, at the start she did not travel from Italy to Buenos Aires with a chaperon but eloped with a bass baritone who became her maestro for the next fourteen years. The 'Florentine Nightingale' triumphed throughout South America and went on to do the same in Russia where, in St. Petersburg, she sang with Caruso. Then in San Francisco she began her conquest of the United States. After initial refusals by Covent Garden to let her sing, she was eventually allowed to appear out of season in Melba's absence; her debut was sensational, she was heralded as 'the voice of the century' and the United Kingdom too fell under her spell.